Implementation of Occupational Safety and Health (OSH) Office Program in Community Health Center - Eko Prasetyo; Ulya, Tis’aTul; David Laksamana Caesar; Ervi Rachma Dewi; Livana PH (Journal Of Nursing Practice, 2025)
Background: Office OSH includes all activities that guarantee and protect the safety and health of employee work so that they do not experience work accidents or diseases related to their work at work. Purpose: To determine the description of office OSH policies, work safety standards, work health standards, office work environment health and office ergonomics at the Ngembal Kulon Health Center, Kudus Regency. Methods: This study is study qualitative with use method descriptive. Technique purposive sampling sample selection and this data collection technique uses interview techniques, observation, and documentation with informant as much as 6 person. The main instrument used in this study was an interview guide on the implementation of office OSH standards at the community health center. Results: The policy OSH in health center still not optimal. Occupational safety standards aspect, that have not been met include hydrants, fire alarms, and box first aid kits. Occupational health standards aspect, are quite good with the implementation of fitness exercises, mental health screening, routine check-ups, and support for exclusive breastfeeding programs for employees. Environmental health standards aspect, the fulfillment of waste management, vector control, and sanitation. Ergonomic standards aspect, the lack of socialization about ergonomic work postures for officers in the health centre. Conclusion: Office OSH is still not optimal based on Permenkes No. 48 of 2016. Need support from District Health Office as the supervisor of implementation OSH offices at health centre. This is very important because it has implications for protection of health workers, patients, and work environment.